Dual Energy CT Imaging in Cone-Beam Micro-CT for Improved Attenuation Coefficient Measurement - 唐智伟 胡广书 (Tsinghua science and technology, 2011)
In order to improve micro-CT＇s capability of accurate quantification of linear attenuation coefficient μ, a dual energy method was developed to correct beam hardening artifacts caused by the polychromatic spectra of X-ray tubes. In this method, two sets of scans, taken at different energy levels, were combined to create a synthetic monochromatic image. A physical polychromatic model of μ in dual energy imaging was developed with an iterative method to solve the model for a few selected pixels. To find a high-speed and effective computing approach, the physics model was approximated by a polynomial function of the measured intensities. The method was tested on a PMMA-aluminum phantom and CaCI2 admixtures. The results show that streak and cupping artifacts are completely eliminated and that the measurement of the reconstructed attenuation coefficient μ is observed to be over 95% accurate.